Interaksi Kinerja Keuangan dalam Meningkatkan Nilai Perusahaan (Studi pada Subsektor Makanan dan Minuman yang Tercatat di BEI Periode 2019-2021) - Dimas Adi Wicaksono; Hani Krisnawati; Praditya Dewi Arumsari (Jurnal Bingkai Ekonomi (JBE), 2022)
This study was conducted to test the determination of leverage on firm value with firm performance as a moderating variable. Contribution to science in an effort to increase company value is expected to be realized from the basic model of this study. The model was tested on 17 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Purposive sampling is done as a method in determining the sample of a data, as well as an absolute difference analysis approach using SPSS software to determine the effect of moderation. The results of this study indicate that leverage and financial performance have an influence on firm value, and the moderating effect of financial performance has no effect on strengthening or weakening leverage on firm value.